Experiences of elderly patients regarding participation in their hospital discharge: a qualitative metasummary. Issue 11 (3rd November 2019) - Lilleheie, Ingvild; Debesay, Jonas; Bye, Asta; Bergland, Astrid
Abstract : Background: Ageing patients are discharged from the hospital 'quicker and sicker' than before, and hospital discharge is a critical step in patient care. Older patients form a particularly vulnerable group due to multimorbidity and frailty. Patient participation in healthcare is influenced by government policy and an important part of quality improvement of care. There is need for greater insights into the complexity of patient participation for older patients in discharge processes based on aggregated knowledge. Objective: The aim of this study was to review reported evidence concerning the experiences of older patients aged 65 years and above regarding their participation in the hospital discharge process. Methods: We conducted a qualitative metasummary. Systematic searches of Medline, Embase, Cinahl, PsycINFO and SocINDEX were conducted. Data from 18 studies were included, based on specific selection criteria. All studies explored older patients' experience of participation during the discharge process in hospital, but varied when it came to type of discharge and diagnosis. The data were categorised into themes by using thematic analysis. Results: Our analysis indicated that participation in the discharge process varied among elderly patients. Five themes were identified: (1) complexity of the patients state of health, (2) management and hospital routines, (3) the norm and preference of returning home, (4) challenges of mutual communication and asymmetric relationships and (5) the significance of networks. Conclusions: Collaboration between different levels in the health systems and user-friendly information between staff, patient and families are crucial. The complexity of patient participation for this patient group should be recognised to enhance user involvement during discharge from hospital. Interventions or follow-up studies of how healthcare professionals can improve their communication skills and address the tension between client-centred goals and organisational priorities are requested. Organisational structure may need to be restructured to ensure the participation of elderly patients.